EGG INCUBATION AND QUALITY OF YELLOWFIN TUNA (THUNNUS ALBACARES) LARVAE AT DIFFERENT SALINITY - Mawardi, Ichi Naomi; Waspodo, Saptono; Mukhlis, Alis (Program Studi Budidaya Perairan Universitas Mataram, 2022)
This study aims to determine the proper salinity of sea water for egg incubation and maintenance of early yellowfin tuna larvae (Thunnus albacares). This research was conducted in November - December 2017 at Large Marine Research Center and Fisheries Extension of Gondol, Bali. This study used an experimental method with complete randomized design with 4 treatments and 3 replications, namely treatment (A) 29 ppt, (B) 31 ppt, (C) 33 ppt, (D) 35 ppt. Data were analyzed using analysis of variance (ANOVA) with a real level of 5%. The results showed that different salinity during the incubation and maintenance period of yellow fin tuna larvae did not have a significant effect on incubation time, hatchability and total larval length, but had a significant effect on the level of abnormalities of the larvae. Salinity of 35 ppt, with incubation time spent 20 hours 43 minutes, showed egg hatchability of 49.89%, lowest abnormality of 16.03%, and total larval length of 2.82 mm. The conclusion of this study is that salinity for the egg incubation period and maintenance of yellow fin tuna larvae are still in the range 33-35 ppt.